THE ROLE OF VIRTUAL TECHNOLOGIES IN MODERN PROFESSIONAL QUALITIES OF FUTURE TEACHERS OF TECHNOLOGICAL EDUCATION IN HIGHER EDUCATIONAL INSTITUTIONS (World Economics and Finance Bulletin, 2023)
The purpose of the Law "On Education" of the Republic of Uzbekistan is to improve the education system at the world standard level and to train competitive, mature specialists. The concept of electronic education proposed by Bedpool Khan has eight aspects: pedagogical, technological, pedagogical interface design, assessment, management, support for feedback, ethical feedback, and feedback
Keywords: electronic education; modern and systematically thinking